(untitled) (Journal of Surgical Sciences, 2021)
Background: There is evidence that mesh repair for umbilical hernias results in fewer recurrences. Early and late complication rates of mesh repair are variable with different techniques of mesh repair. In recent years, several mesh device for the repair of small ventral hernias have been developed, but some reports have been published reporting some adverse outcomes like high recurrences or wound related complications encountered with those mesh devices. The purpose of this study was to evaluate the safety and efficacy of small umbilical hernia(<3cm) repair using self expanding dual mesh. Methods: In this study we used a composite self-expanding mesh with Polypropylene(PP) on one side and expanded polytetrafleuroethylene(ePTFE) on the other side. We introduced this technique in our department at BIRDEM General Hospital and IMC in March 2017 and collected patients data and outcome in an observational study of 25 consecutive patients matching our inclusion criteria until February 2019. In addition to the routine 1st week postoperative follow-up, We did a prospective follow-up at 1 month,6 month and 1 year which included a questionnaire, clinical examination and ultra sonogram after 12 months. Results: The study included 15 female and 10 male patients with age ranging from 25-62 years(Mean- 47) having 16 primary umbilical hernia and 9 umbilical port hernias. The size of gap was <3cm and all except 2 hernias were reducible. In all patients a self expanding dual mesh was used with a diameter of 8cm(18 patients) or 6.4(7 patients) cm. Early complications included superficial wound infection-1(4%), seroma-1(4%), serosanguinous discharge-1(4%) and ecchymosis-1(4%). No major wound problems were noted in 1 month or 6 month follow-up except 1 patient reporting hypertrophied scar. At 1st month follow up 21 patientswere pain free, after 6 month only 1 patient reported mild pain, after 1 year 100% patients were pain free. 24 out of 25 patients ie 96% were very satisfied with the result of their repair. There was no recurrence after one year. Conclusion: Umbilical and umbilical port hernia repair with Self expanding dual mesh is effective and is cosmetically very appreciated by patients as good as laparoscopic repair. Therefore, we recommend using these meshes only for umbilical and umbilical port hernias smaller than 3 cm. For larger or incisional hernias other techniques allowing the use of larger meshes is advocated. Journal of Surgical Sciences (2020) Vol. 24 (2) : 43-50